PENERAPAN METODE DRILL DALAM PROSES PEMBELAJARAN UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA ARAB KELAS 2 SD PKBM PERMATA SUNNAH SIDOARJO - Muhammad Misbahuddin; Andy Fahmi Halim (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2022)
This study aims to determine the impact of the use of the Drill method in learning Arabic on the improvement of mastery of Arabic vocabulary comprehension for grade 2 students of PKBM Permata Sunnah, Sidoarjo. The Drill method is used by educators because this method is suitable for foreign language learning, especially Arabic learning because students gain vocabulary understanding skills. This study uses the CAR research method, namely classroom action research with a descriptive quantitative approach, as the object of the class 2 students of the PKBM PKBM Permata Sunnah, Sidoarjo. The results of the research carried out showed that the application of the Drill method in Arabic subjects could improve memorization and vocabulary understanding of grade 2 students of the Permata Sunnah PKBM Brotherhood, Sidoarjo. This is evidenced by the student test results from the first test and the second test the percentage of students who can answer increases by 15%.